2014
DOI: 10.1080/00103624.2013.875205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biosolids-Derived Organomineral Fertilizers, Urea, and Biosolids Granules on Crop and Soil Established with Ryegrass (Lolium perenne L.)

Abstract: A pot scale trial investigated the agronomic performance of two organomineral fertilizers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…The work reported here extends earlier studies by Antille et al (2013bAntille et al ( , 2014a conducted at glasshouse-and field-scales on the value of biosolids-derived OMF as amendments for perennial ryegrass (Lolium perenne L.), which showed satisfactory agronomic and environmental performance of OMF, and suggested that such products could be used to extend the use of biosolids on arable land. Consequently, the study reported here assessed the agronomic efficiency and determined the feasibility of using OMF on economically important arable crops, such as winter wheat, grown in the Northwest of England.…”
Section: Organomineral Fertilizerssupporting
confidence: 72%
See 3 more Smart Citations
“…The work reported here extends earlier studies by Antille et al (2013bAntille et al ( , 2014a conducted at glasshouse-and field-scales on the value of biosolids-derived OMF as amendments for perennial ryegrass (Lolium perenne L.), which showed satisfactory agronomic and environmental performance of OMF, and suggested that such products could be used to extend the use of biosolids on arable land. Consequently, the study reported here assessed the agronomic efficiency and determined the feasibility of using OMF on economically important arable crops, such as winter wheat, grown in the Northwest of England.…”
Section: Organomineral Fertilizerssupporting
confidence: 72%
“…Such a response also suggested that fertilizer N-related stresses prior to anthesis occurred to lesser extent in urea-and OMF-compared with biosolids-treated crop. This is because of faster N release and enhanced uptake in those treatments (Antille et al, 2013b(Antille et al, , 2014a following fertilizer application in spring, with subsequent N remobilization at later stages of crop development. Poorer physical properties of OMF 15 compared to OMF 10 in the batch applied in 2008 also explain relative differences in use-efficiency between the two materials (Jensen and Pesek, 1962).…”
Section: Discussion Fertilizer Application Effects On Cropmentioning
confidence: 99%
See 2 more Smart Citations
“…A soil analysis conducted 120 days after the OMFs treatment showed the decrease of soil organic nitrogen; this can be attributed to the N-immobilization and gaseous losses, which are the result of denitrification process. The losses of nitrogen resulting from the volatilization of ammonia can occur within a surface application of fertilizers [77]. A correlation between nitrogen uptake and nitrogen rate was observed.…”
Section: Organo-mineral Fertilizers With Sewage Sludgementioning
confidence: 89%